Prone positioning redistributes gravitational stress in the lung in normal conditions and in simulations of oedema. Issue 7 (6th January 2021) - Kizhakke Puliyakote, Abhilash S.; Holverda, Sebastiaan; Sá, Rui C.; Arai, Tatsuya J.; Theilmann, Rebecca J.; Botros, Liza; Bogaard, Harm J.; Prisk, G. Kim; Hopkins, Susan R.
Abstract : New Findings: What is the central question of this study? How does the interaction between posture and gravity affect the stresses on the lung, particularly in highly inflated gravitationally non‐dependent regions, which are potentially vulnerable to increased mechanical stress and injury? What is the main finding and its importance? Changes in stress attributable to gravity are not well characterized between postures. Using a new metric of gravitational stress, we show that regions of the lung near maximal inflation have the greatest gravitational stresses while supine, but not while prone. In simulations of increased lung weight consistent with severe pulmonary oedema, the prone lung has lower gravitational stress in vulnerable, non‐dependent regions, potentially protecting them from overinflation and injury. Abstract: Prone posture changes the gravitational vector, and potentially the stress induced by tissue deformation, because a larger lung volume is gravitationally dependent when supine, but non‐dependent when prone. To evaluate this, 10 normal subjects (six male and four female; age, means ± SD = 27 ± 6 years; height, 171 ± 9 cm; weight, 69 ± 13 kg; forced expiratory volume in the first second/forced expiratory volume as a percentage of predicted, 93 ± 6%) were imaged at functional residual capacity, supine and prone, using magnetic resonance imaging, to quantify regional lung density. We defined regional gravitational stress as the cumulative weight, per unit area, of the column of lung tissue below each point. Gravitational stress was compared between regions of differing inflation to evaluate differences between highly stretched, and thus potentially vulnerable, regions and less stretched lung. Using reference density values for normal lungs at total lung capacity (0.10 ± 0.03 g/ml), regions were classified as highly inflated (density < 0.13 g/ml, i.e., close to total lung capacity), intermediate (0.13 ≤ density < 0.16 g/ml) or normally inflated (density ≥ 0.16 g/ml). Gravitational stress differed between inflation categories while supine (−1.6 ± 0.3 cmH2 O highly inflated; −1.4 ± 0.3 cmH2 O intermediate; −1.1 ± 0.1 cmH2 O normally inflated; P  = 0.05) but not while prone (−1.4 ± 0.2 cmH2 O highly inflated; −1.3 ± 0.2 cmH2 O intermediate; −1.3 ± 0.1 cmH2 O normally inflated; P  = 0.39), and increased more with height from dependent lung while supine (−0.24 ± 0.02 cmH2 O/cm supine; −0.18 ± 0.04 cmH2 O/cm prone; P  = 0.05). In simulated severe pulmonary oedema, the gradient in gravitational stress increased in both postures (all P  < 0.0001), was greater in the supine posture than when prone (−0.57 ± 0.21 cmH2 O/cm supine; −0.34 ± 0.16 cmH2 O/cm prone; P  = 0.0004) and was similar to the gradient calculated from supine computed tomography images in a patient with acute respiratory distress syndrome (−0.51 cmH2 O/cm). The non‐dependent lung has greater gravitational stress while supine and might be protected while prone, particularly in the presence of oedema.